Value Creation Through Order-To-Cash System Collaboration at Pt. Bukit Muria Jaya - Fadjar Andi Wibowo; Prof. Roy Sembel, Ph.D (Sekolah Tinggi Manajemen IPMI, 2019)
Any business entity generally aims for value creations as one of the business objectives. Nowadays, value creation is increasingly represented as intangible drivers like innovation, people, ideas, product for the company and chain-networks (customers and suppliers). Creating value for customers by helping in selling the products and services are beyond the traditional methods. In overall perspective, value creation is a better management goal whose intention is to create cost-reduction, increase service level and profitability that enhance long-term competitiveness and sustainable business growth. This study focused on the understanding the “value creation initiative through order-to-cash system collaboration at PT BukitMuriaJaya (BMJ)” to customers with objectives to increase value proposition, response customer voice of improvement regarding low-score KPI on value-creation criteria, and leverage company value proposition for sustainable business partnership. This study applies a qualitative approach by conducting a series of a personal interview with company top management, experts in selected functions and key buyers in selected customers. The interview results were analyzed through relevant theoretical frameworks, company primary data's and secondary data from various sources. Last but not least, the result of the analysis will lead to made conclusions and recommendations to the company. To maintain company reputation and position in the market In the near future, BMJ should focus on increasing value proposition by generating value creation initiatives and finally answering customer voices for improvement.